Influencing factors in teachers’ organizational commitment: A systematic review - Marco Antonio Alvarado Figueroa; Luis Miguel Romero Echevarria; Georgina Alejandrina Pinto Sotelo; Marlene Cusi Montesinos; Luis Alberth Rossel Bernedo (International Journal of Medical Toxicology and Legal Medicine, 2024)
The role of teachers is fundamental in the development of talent and organisations are increasingly concerned with fostering their organizational commitment. For the present study, a systematic review was carried out to identify the factors influencing teachers’ organizational commitment. In this process, the PRISMA diagram was used for an exhaustive search of documents, from which twenty relevant articles obtained from SciELO (4) and Scopus (16) were selected. In conclusion, it was found that the organizational commitment of teachers is a complex aspect that affects the stability of the organization and the factors influencing its promotion are psychological, managerial and recognition factors.